Front Cover: Dehydrogenative Coupling of a Tertiary Silane Using Wilkinson's Catalyst (Eur. J. Inorg. Chem. 18/2016). Issue 18 (28th June 2016) - Azpeitia, Susan; Fernández, Belén; Garralda, María A.; Huertos, Miguel A.
Abstract : The cover picture shows the dehydrocoupling of a tertiary silane catalyzed by Wilkinson's catalyst. The hydrosilane used as substrate in this reaction has two thioether moieties, which are useful to synthesize an active species in the catalytic cycle, such as the silylhydridorhodium(III) complex, whose structure is shown on the left. As a result of this work, a simplified mechanism can be proposed, and this can be key to a better understanding of the dehydrogenative coupling of silanes catalyzed by late transition metals. Details are discussed in the article by M. A. Huertos et al. onp. 2891 ff. For more on the story behind the cover research, see theCover Profile .